On human nature : biology, psychology, ethics, politics, and religion - Tibayrenc, Michel; Ayala, Francisco J. (Francisco Jose), 1934-2023 (Academic Press, 2017)
"Covers the present state of knowledge on human diversity and its adaptive significance through a broad and eclectic selection of representative chapters. This transdisciplinary work brings together specialists from various fields who rarely interact, including geneticists, evolutionists, physicians, ethologists, psychoanalysts, anthropologists, sociologists, theologians, historians, linguists, and philosophyers. Genomic diversity is covered in several chapters dealing with biology, including the differences in man and apes and the genetic diversity of mankind. Top specialists, known for their open mind and broad knowledge, have been carefully selected to cover each topic. The book is therefore at the crossroads between biology and human sciences, going beyond classical science in the Popperian sense. It is accessible not only to specialists, but also to students, professors, and the educated public. Glossaries of specialized terms and general public references help non-specialists understand complex notions, with contributions that avoid technical jargon"--Publisher's description